Auditing Certification Schemes on Sustainability - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (Universiti Putra Malaysia, 2014)
KUALA LUMPUR, 17 NOV - The Roundtable on Sustainable Palm Oil (RSPO) in partnership with Malaysia’s pioneer tertiary education institution in agriculture, Universiti Putra Malaysia (UPM) have agreed to launch a course on Auditing Certification Schemes on Sustainability.